Sport specialization and burnout symptoms among adolescent athletes - Benedikt Hösl; Hannah Oberdorfer; Martin Niedermeier; Martin Kopp (International Journal of Adolescence and Youth)
Specializing in a single sport may contribute to athlete burnout. The aim of this study was to compare adolescents who specialized in a sport and those without specialization in terms of athlete burnout. Furthermore, potential gender differences and the association between burnout and well-being were investigated. Using a cross-sectional survey, 169 adolescent athletes (Mage = 16.29 years) were asked about sport specialization, athlete burnout symptoms, and psychological well-being. Non-specialized athletes reported significantly lower scores in the burnout dimension emotional/physical exhaustion (p = .030,d = -0.34), and significantly higher scores in the devaluation (p = .008,d = 0.42) and reduced sense of accomplishment dimension (p = .036,d = 0.33) than specialized athletes. Females generally showed higher burnout scores, but no significant specialization*gender interactions were found. Athlete burnout was negatively related to psychological well-being. Early warning signs should be monitored in athletes who specialize in a single sport to prevent burnout-related exhaustion; independent of this, female athletes should be particularly aware of burnout symptoms.